Pengembangan Framework Pelaporan Cyber Crime - Daryono Daryono; Bambang Sugiantoro (UIN Sunan Kalijaga Yogyakarta, 2017)
In the era of globalization, technological development is very rapid, Information and Communication Technology (ICT) has become part of human life that can not be separated. where ICTs make our lives easier and more enjoyable. But ICTs can also be used for the crime. cybercrime is a criminal offense which is done by using computer technology as a major crime.From the information above there are many communities that use the gadget Ranging from Mobile, Smartphones, Tablets, Laptops and PCs are already connected to the Internet, there are still many people who experience crime Cybercrime ignorance of knowledge. Indonesian people themselves to report kepihak responsible for dealing with cases of cyber crimes and their reluctance to report for dikepolisian procedures are so complicated and for reporting model that still konvensional.Maka here the author makes a framework for reporting cybercrime police kepihak so that people easily and quickly in report, if there are victims of crime cyber.penelitian was conducted in this study Surakarta.metode city Mapolresta menggembangkan from a previous study conducted by Shin Yong-dalNew models for cyber crime investigation Procedure, namely the framework stages of handling cases of cyber crime.hasil development that the writers are making cybercrime reporting framework using informasi.dengan system information system cybercrime report, then the public will quickly and easily in the report, if it becomes a victim of cyber , as well as the police was quick to respond and when a report from society.